Noncoding RNAs in rheumatoid arthritis: modulators of the NF-κB signaling pathway and therapeutic implications - Seyedi, Dina; Espandar, Najmadin; Hojatizadeh, Maryam; Mohammadi, Yaser; Sadri, Farzad; Rezaei, Zohreh (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that causes joint inflammation and gradual tissue destruction. New research has shown how important noncoding RNAs (ncRNAs) are for changing immune and inflammatory pathways, such as the WNT signaling pathway, which is important for activating synovial fibroblasts and osteoblasts to work. This article examines the current understanding of several ncRNAs, such as miRNAs, lncRNAs, and circRNAs, that influence NF-κB signaling in the pathogenesis of RA. We investigate how these ncRNAs impact NF-κB signaling components, altering cell proliferation, differentiation, and death in joint tissues.The paper also looks at how ncRNAs can be used as potential early detection markers and therapeutic targets in RA because they can change important pathogenic pathways. This study highlights the therapeutic potential of targeting ncRNAs in RA therapy techniques, with the goal of reducing inflammation and stopping disease progression. This thorough analysis opens up new possibilities for understanding the molecular foundations of RA and designing novel ncRNA-based treatments.